Eco-friendly Products and Practices-A Key to Successful Organic Farming - Lakshman, K.; Veerendra, M.; Nataraj, K. C.; Naseeruddin, R.; Naik, N. Ramesh; Deva, Sahaja; Reddy, B. Sahadeva (Chronicle of Bioresource Management, 2024)
Organic farming is gaining paramount importance from the recent past. It minimizes environmental pollution by eliminating toxic chemicals and improves the quality of produce besides fetching remunerative price. Thus, farmers are highly passionate and getting attracted for growing organic food. Adopting organic farming is essential for a sustainable future since it ensures the planet’s long-term health and the welfare of future generations.However, the inputs used in organic production is purchased from the input dealers at higher prices, as the farmers lack awareness about the eco-friendly products, their ingredients and preparations. Use of biological agents, plant-based extracts, cow-based preparations, microbial consortia, and other similar items are environmentally acceptable and readily available in the local market, which costs very less if prepared by the farmer himself.